Good Corporate Governance Sebagai Variabel Intervening Antara Manajemen Laba Dengan Nilai Perusahaan - Christiana, Irma; Ardila, Isna (Jurnal Ilmu Manajemen, 2020)
Good corporate governance is interpreted as a rule that underlies the process and procedures of company management in accordance with the laws and business ethics. The purpose of the research is to examine the effect of earnings management on firm value with good corporate governance as an intervening variable on insurance companies listed on the Indonesia Stock Exchange. In order to answer the hypothesis, this study uses an associated quantitative method. The sampling technique was using purposive sampling method so that 8 companies were selected that met the criteria of a population of 14 companies, with data on gender and time series. Data analysis using regression and path analysis in the form of Sobel test. The findings of this study are that partially good corporate governance is not influenced by earnings management. Another thing that is found is that individually earnings management and good corporate governance do not affect the value of the company. By using the Sobel test to test the hypothesis obtained results that good corporate governance is not able to mediate between earnings management with firm value